2018
DOI: 10.1126/science.aar3617
|View full text |Cite
|
Sign up to set email alerts
|

Probing magnetism in 2D van der Waals crystalline insulators via electron tunneling

Abstract: Magnetic insulators are a key resource for next-generation spintronic and topological devices. The family of layered metal halides promises varied magnetic states, including ultrathin insulating multiferroics, spin liquids, and ferromagnets, but device-oriented characterization methods are needed to unlock their potential. Here, we report tunneling through the layered magnetic insulator CrI as a function of temperature and applied magnetic field. We electrically detect the magnetic ground state and interlayer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
752
4
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 815 publications
(799 citation statements)
references
References 42 publications
37
752
4
6
Order By: Relevance
“…The MOKE signal of the bilayer is seen to suppress strongly, indicating an interlayer antiferromagnetic coupling with zero out‐of‐plane magnetization, which could be related to and favored by a monoclinic stacking at low temperatures. This finding was later verified in tunneling heterostructures comprised of graphite/CrI 3 /graphite/h‐BN, as shown in Figure C . Consistent with MOKE measurements, electron tunneling was also suppressed in the antiferromagnetic configuration.…”
Section: Progress On Van Der Waals Magnets and Heterostructuressupporting
confidence: 75%
See 2 more Smart Citations
“…The MOKE signal of the bilayer is seen to suppress strongly, indicating an interlayer antiferromagnetic coupling with zero out‐of‐plane magnetization, which could be related to and favored by a monoclinic stacking at low temperatures. This finding was later verified in tunneling heterostructures comprised of graphite/CrI 3 /graphite/h‐BN, as shown in Figure C . Consistent with MOKE measurements, electron tunneling was also suppressed in the antiferromagnetic configuration.…”
Section: Progress On Van Der Waals Magnets and Heterostructuressupporting
confidence: 75%
“…C, Schematic view of the electronic tunneling device (upper panel). Zero bias conductance verses magnetic field for a bilayer CrI 3 (lower panel) . D, RMCD signal mapping verses back gate and top gate voltage for gated bilayer CrI 3 device .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, to the purpose of spintronics applications, extensive efforts have been devoted to introduce magnetism to pristine graphene, but the distribution of the magnetic ions is sensitively dependent on the synthesis procedure, not to mention problems such as the low solubility and surface clustering . Yet CrI 3 atomically thin layers stand out not only because of the innate ferromagnetic nature but also the extremely huge magneto resistance (10 000%), which might be a remarkable breakthrough in the spintronics field.…”
Section: Magnetic Moment (μB) For Cri3 Monolayer From Gga+u (Ucr = 5mentioning
confidence: 99%
“…It was also theoretically reported that 1T phase CrS 2 exhibits a striped antiferromagnetic to ferromagnetic transition when going from a ML to bilayer and thicker CrS 2 . Moreover, it was reported that chromium (Cr)‐containing 2D layers, such as CrI 3 and Cr 2 Ge 2 Te 6 , exhibit ferromagnetic order and that devices made of such layers showed novel tunneling magnetoresistance characteristics . Cr‐containing 2D layers are becoming a heavily researched direction in the 2D‐materials field aiming to develop low‐power ultra‐compact spintronic applications.…”
Section: Introductionmentioning
confidence: 99%